Global land-use and sustainability implications of enhanced bioenergy import of China. (15th April 2023) - Wu, Yazhen; Deppermann, Andre; Havlík, Petr; Frank, Stefan; Ren, Ming; Zhao, Hao; Ma, Lin; Fang, Chen; Chen, Qi; Dai, Hancheng
Graphical abstract: Source of additional bioenergy supply for China's 1.5℃ climate target under two multi-region supply scenarios Highlights: Global land-use impacts of China's bioenergy import schemes were explored. Major sustainability concerns arise when relying on any single market for biomass import. Economically optimized biomass import can partly mitigate sustainability tradeoffs. Abstract: Most ambitious climate change mitigation pathways indicate multifold bioenergy expansion to support the energy transition, which may trigger increased biomass imports from major bioenergy-consuming regions. However, the potential global land-use change and sustainability trade-offs alongside the bioenergy trade remain poorly understood. Here, we apply the Global Biosphere Management Model (GLOBIOM) to investigate and compare the effects of different increasing bioenergy import strategies in line with the 1.5℃-compatible bioenergy demand in China, which is projected to represent 30% of global bioenergy consumption by the middle of the century. The results show that sourcing additional bioenergy from different world regions could pose heterogeneous impacts on the local and global land systems, with implications on food security, greenhouse gas emissions, and water and fertilizer demand. In the worst cases under strict trade settings, relying on biomass import may induce up to 25% of unmanaged forests converted to managed ones in the supplying regions, while in an open trade environment, increasing bioenergy imports would drastically change the trade flows of staple agricultural or forestry products, which would further bring secondary land-use changes in other world regions. Nevertheless, an economically optimized biomass import portfolio for China has the potential to reduce global overall sustainability trade-offs with food security and emission abatement. However, these benefits vary with indicator and time and are conditional on stricter land-use regulations. Our findings thus shed new light on the design of bioenergy trade strategies and the associated land-use regulations in individual countries in the era of deep decarbonization.